Serial 3 orthogonal lead electrocardiographic abnormalities after pulmonary embolism. Computer assisted study. Issue 6 (June 1976) - Dunn, F; Henderson, A; Macfarlane, P W; Moran, F; Lawrie, T D
Abstract : The 3 orthogonal lead electrocardiogram has been evaluated with computer assisted interpretation in 20 patients with acute pulmonary embolism confirmed by pulmonary angiography. Initial 3-lead electrocardiographic abnormalities were found to be at least as helpful as the 12-lead electrocardiogram in supporting the clinical diagnosis. In addition, however, sequential changes in both the maximum QRS and T vector orientations in frontal and transverse planes were more often apparent than any sequential changes in the 12-lead electrocardiogram. While no specific 3 lead electrocardiographic criterion for pulmonary embolism could be determined, this technique was more helpful than conventional methods in following serial electrocardiographic changes in patients with this condition.